(untitled) (Bulletin of Innovative Research, 2026)
This article examines the specifics of the guilt motif and its connection with suffering in the novels of F.M. Dostoevsky. Suffering is viewed as a natural consequence of guilt and simultaneously as a path to spiritual rebirth. It is shown that guilt in Dostoevsky is not only a legal or moral category, but, above all, an ontological state of a person.